Polytrauma is Associated with Worse 3- and 6-month Disability After Traumatic Brain Injury: A TRACK-TBI Pilot Study. (16th November 2020) - Yue, John K; Satris, Gabriela; Dalle Ore, Cecilia L; Huie, J. Russell; Deng, Hansen; Winkler, Ethan A; Lee, Young M; Vassar, Mary; Taylor, Sabrina; Schnyer, David M; Lingsma, Hester F; Puccio, Ava; et al.
Abstract: INTRODUCTION: Polytrauma is common in traumatic brain injury (TBI). The Glasgow Outcome Scale-Extended (GOSE) remains the most widely used TBI outcome measure, however peripheral injuries from polytrauma may confound measurement of TBI-specific outcome using the GOSE. METHODS: Adult subjects from the prospective, multicenter TRACK-TBI Pilot study who completed 3- and 6-month GOSE were included. Polytrauma was the variable of interest (AIS ≥ 3 in any extracranial system). Univariate ordinal and logistic regressions were performed using clinical GOSE cutoffs. Multivariable ordinal regressions were performed for 3- and 6-month GOSE, controlling for known predictors (age, sex, race, education, psychiatric history, high-speed mechanism, GCS, Marshall CT score). Odds ratios (OR) and [95% CIs] are reported. RESULTS: Overall, 361 subjects were aged 44.9 ± 18.9-years, 69.8% were male, 80.6% were Caucasian, and 19.1% had polytrauma. By GCS, 80.1% were mild TBI, 5.8% were moderate, and 14.1% were severe. Marshall CT score distribution was Marshall = 1 (48.2%), Marshall = 2 (37.4%), Marshall = 3-4 (8.0%), Marshall = 5-6 (6.4%). Polytrauma patients generally had more severe TBI (33.3% vs. 9.6%), less mild TBI (60.9% vs. 84.6%), and more high-speed injuries (motor vehicle/pedestrian struck, 68.1% vs. 29.1%). At 3-months, GOSE included expired (GOSE = 1, 5.5%), vegetative/severe disability (GOSE = 2-4, 9.4%), lower moderate disability (GOSE = 5, 12.5%), upper moderate disability (GOSE = 6, 14.7%), lower good recovery (GOSE = 7, 30.7%), upper good recovery (GOSE = 8, 27.1%); the 6-month GOSE distribution was 6.4%, 6.4%, 11.6%, 17.2%, 27.7%, and 30.7%, respectively. Compared to isolated TBI, more patients with polytrauma declined from 3-to-6 months (37.7% vs. 24.7%), while fewer patients improved (11.6% vs. 22.6%, P = . 033). On univariate logistic regression, polytrauma associated with increased odds of moderate disability or worse (GOSE ≤ 6) (3-month OR = 2.57 [1.50-4.41]; 6-month OR = 1.70 [1.01-2.88]), and death/severe disability (GOSE ≤ 4) (3-month OR = 3.80 [2.03-7.11]; 6-month OR = 3.33 [1.71-6.46]). Polytrauma had greater univariate ordinal odds for poorer GOSE (3-month OR = 2.79 [1.73-4.49]; 6-month OR = 1.73 [1.07-2.79]), which was conserved on multivariable regression (3-month OR = 3.05 [1.76-5.26]; 6-month OR = 2.04 [1.18-3.42]). CONCLUSION: TBI patients with polytrauma are at greater risk for 3- and 6-month disability. Methodological improvements in assessing TBI-specific disability, versus disability attributable to systemic injuries, will generate better outcomes assessment tools in modern TBI care and research.